3D printed modeling contributes to reconstruction of complex chest wall instability. (August 2019) - Bergquist, John R.; Morris, Jonathan M.; Matsumoto, Jane M.; Schiller, Henry J.; Kim, Brian D.
Abstract: Background: Three-dimensional printed models are increasingly used in many fields including medicine and surgery, but their use in the planning and execution of complex chest wall reconstruction has not been adequately described. In cases of non-union or prior attempts at chest wall reconstruction which have failed, there can be substantial deviations from expected chest wall anatomy. We report a novel technique for pre-operative planning and surgical execution of complex chest wall reconstruction, assisted by 3D printing. Our objective was to utilize 3-D volumetric modeling coupled with 3-D printing to produce patient-specific models for chest wall reconstruction in complex cases. Methods: Soft tissue reconstruction 0.75 mm slice thickness computed tomography (CT) imaging data was loaded into medical CAD software for segmentation. Lung, muscle, foreign bodies, and bony structureswere separated due to the differences in density between them. The 3D volumetric mesh was then quality checked and stereolithography files (STL) were made which were able to be utilized by the 3D printer. The STL files were exported to a Objet 500 material jetting printer that utilized several UV light cured photopolymers. Results: As an example case, we discuss a 55 year old male who underwent resuscitative thoracotomy. In the early post-operative period, he developed a pulmonary hernia in the 6th intercostal space, repaired with wire cerclage reapproximation of ribs. He developed a symptomatic mobile chest wall at the site of prior repair with additional concern for dissociated anterior cartilage. In preparation for operative repair, a 3D printed model was created, demonstrating fractured cartilage anteriorly as well a saw effect through the six and seventh ribs. An additional model was created using the normal ribs from the right side in mirror image reflection to quantify the degree and precise geometry of mal-alignment to the left chest. These models were then utilized to determine the operative approach via a thoracotomy incision to remove the cerclage wires, followed by parasternal incision, reduction and plating of the sternocostal non-union bursa Rib non-unions were plate stabilized. Repeat imaging in follow-up has demonstrated continued appropriate alignment and the patient reported improvement in his symptoms. Conclusion: At present, the cost of 3-D printing remains substantial, but given the improved planning in complex cases, this cost may be recaptured in the reduction of operative time and improved outcomes with reduced re-operation rates. We believe that the early adoption of this technology by surgeons can help improve surgical quality and provide enhanced individualized patient care. These patient-specific models facilitate identification of features which are often not detected with standard 3-D reconstructed CT rendering. Centers should pursue the integration of 3-D printed models into their practice and active collaborations between surgeons and modeling experts should be sought at every available opportunity.